2008
DOI: 10.1111/j.1462-2920.2008.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Light affects motility and infectivity of Agrobacterium tumefaciens

Abstract: Response to changes in light conditions involves a variety of receptors that can modulate gene expression, enzyme activity and/or motility. For the study of light-regulated effects of Agrobacterium tumefaciens, we used a global analysis approach - proteomics - and compared the protein patterns of dark- and light-grown bacteria. These analyses revealed a significant reduction of FlaA and FlaB - proteins of the flagellum - when the cells were grown in light. The light effect was confirmed by SDS-PAGE with isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 51 publications
5
78
1
Order By: Relevance
“…S3A). Some components of the flagella were more abundant in dark-grown than in irradiated cells, as previously observed in Agrobacterium tumefaciens (31). The observed protein bands were identified by mass spectrometry as FlaA (30.97 kDa) and FlaB (31.18 kDa) flagellin proteins and hook components FlgE (44.44 kDa) and FlgK (52.13 kDa), products of the RL0718, RL0719, RL0728, and RL0729 genes, respectively.…”
Section: R Leguminosarum Has a Lov-hk Proteinsupporting
confidence: 71%
“…S3A). Some components of the flagella were more abundant in dark-grown than in irradiated cells, as previously observed in Agrobacterium tumefaciens (31). The observed protein bands were identified by mass spectrometry as FlaA (30.97 kDa) and FlaB (31.18 kDa) flagellin proteins and hook components FlgE (44.44 kDa) and FlgK (52.13 kDa), products of the RL0718, RL0719, RL0728, and RL0729 genes, respectively.…”
Section: R Leguminosarum Has a Lov-hk Proteinsupporting
confidence: 71%
“…Bacteria cultured in the light had a reduced number of flagella (one or two compared with three to five in the dark) and exhibited reduced mobility in colony assays. Importantly, virulence was also directly affected by light; reduced root attachment was observed in tomato (Solanum lycopersicum) and smaller tumor formation in cucumber (Cucumis sativus) in the presence of light compared with darkness (Oberpichler et al, 2008). Two putative phytochromes and one cryptochrome have been identified in the A. tumefaciens genome (Goodner et al, 2001), but knockout mutants showed normal light-dependent regulation of Fla protein levels (Oberpichler et al, 2008), suggesting that an as yet unidentified photoreceptor may be involved in this process.…”
Section: Light As a Determinant Of Virulence In Pathogensmentioning
confidence: 99%
“…However, the vulnerability of the susceptible host and the virulence of the pathogen may vary both with developmental stage and time of day, thus affecting the outcome of the interaction. The importance of light with respect to the outcome of plant-pathogen interactions is becoming increasingly apparent; recent reports have shown direct effects of light on the both the defense response in the host and on the virulence of the attacking pathogen (Chandra-Shekara et al, 2006;Griebel and Zeier, 2008;Oberpichler et al, 2008). In addition, there is growing realization that circadian rhythms may play an important role in disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light regulation of motility in Agrobacterium tumefaciens (36) and Acinetobacter baylyi (M. Bitrian and B. C. Nudel, unpublished experiments) are recent examples. In this respect, it is relevant to mention that RsbP and RsbQ form a bicistronic operon, not only in B. subtilis (11) but in many other organisms as well, be it that the phosphatase domain can be substituted by other output modules like histidine protein kinases or guanylate cyclases (10).…”
Section: Thementioning
confidence: 99%